CONTRACEPTIVE USAGE AMONG UNDERGRADUATE FEMALE STUDENTS: A SURVEY SAMPLING APPROACH - A. O., . Adepetun (university of eloued جامعة الوادي, 2020)
In this paper, a survey sampling on contraceptive usage among the female undergraduates of Federal University of Technology, Akure using the randomized response technique proposed by Warner [1] was extensively carried out. The data for the study was obtained from the administration of well-structured survey questionnaires on respondents from three different schools in the University. Consequently, the estimated Warner’s proportions of female undergraduate students who used contraceptives and their resulting variances were evaluated at varying sample sizes and predetermined probabilities 𝑃 respectively. The results as presented in the summary table 10 revealed that contraceptive usage was at maximum level for School of Agriculture and Agricultural Technology as sample sizes varied.
articl
Keywords: Randomized response technique, contraceptives, estimated Warner’s proportion, sensitive attribute